2015
DOI: 10.1039/c4cs00177j
|View full text |Cite
|
Sign up to set email alerts
|

Upconverting nanoparticles: assessing the toxicity

Abstract: Lanthanide doped nanoparticles (Ln:NPs) hold promise as novel luminescent probes for numerous applications in nanobiophotonics. Despite excellent photostability, narrowband photoluminescence, efficient anti-Stokes emission and long luminescence lifetimes, which are needed to meet the requirements of multiplexed and background free detection at prolonged observation times, concern about their toxicity is still an issue for both in vivo and in vitro applications. Similar to other chemicals or pharmaceuticals, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
428
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 550 publications
(436 citation statements)
references
References 172 publications
5
428
1
2
Order By: Relevance
“…As proven by the example of gold colloid, which is probably the best-studied nanomaterial to date, these NPs generally are recognized as benign and safe but some forms, that is, specific sizes or with some coating molecules, can be toxic. 227,228 Similarly, lanthanide-doped NPs are basically considered safe, owing to both their chemical composition and size, 180 but their dissolution may potentially become a problem if toxic Gd 3+ ions are part of their composition.…”
Section: Toxicity Of Nir Npsmentioning
confidence: 99%
“…As proven by the example of gold colloid, which is probably the best-studied nanomaterial to date, these NPs generally are recognized as benign and safe but some forms, that is, specific sizes or with some coating molecules, can be toxic. 227,228 Similarly, lanthanide-doped NPs are basically considered safe, owing to both their chemical composition and size, 180 but their dissolution may potentially become a problem if toxic Gd 3+ ions are part of their composition.…”
Section: Toxicity Of Nir Npsmentioning
confidence: 99%
“…Nonetheless, when working with nano-sized materials, it is important to consider several other physicochemical features that might have a toxic effect, including doping, hydrodynamic size, morphology, size heterogeneity, tendency for aggregation, surface functionalization, surface charge, solubility, and biodegradability [179][180][181][182][183]. A significantly lower number of reports are found that study these aspects in detail.…”
Section: Toxicitymentioning
confidence: 99%
“…Review papers summarizing the studies performed on the toxicity of different photoluminescent nanoparticles have been reported, including gold nanoparticles [193][194][195][196], QDs [197][198][199][200][201], lanthanide-based nanoparticles [179,[202][203][204], and C-dots [205]. However, individual toxicity evaluations need to be completed for each developed nanoplatform to completely assure its safety for biomedical applications.…”
Section: Toxicitymentioning
confidence: 99%
“…Inasmuch as there are no endogenous chromophores that significantly absorb near-infrared light of this wavelength, the optical penetration is sufficient to homogenously irradiate larger bulks of tissue. The drawback of this technique is that another exogenous pharmacological entity (i.e., upconverting nanoparticles) must be co-administered with the PS, which may lead to systemic or local toxicity issues [208].…”
Section: Light Sourcementioning
confidence: 99%